Pengaruh Penguatan Pendidikan Karakter Berbasis Al-Quran Dan Kecerdasan Emosional Terhadap Keseimbangan Perilaku Akademik Dan Sosial Jamaah Masjid Al Fattaah Delta Tama Sidoarjo - Mochammad Yoyok Adianto; Nanang Kosim; Muhammad Riyadi; Muhammad Alfi Syahrin (JURNAL PENELITIAN DAN EVALUASI PENDIDIKAN, 2026)
This study aims to analyze the influence of Qur’an-based character education strengthening and emotional intelligence on the balance of academic and social behavior among the congregation of Al Fattaah Mosque, Delta Tama Sidoarjo. The study employed a quantitative approach with a correlational research design. The sample consisted of 30 respondents selected through purposive sampling. Data were collected using closed-ended questionnaires with a Likert scale, while data analysis was conducted using multiple linear regression assisted by IBM SPSS Statistics. The analysis procedures included classical assumption tests, partial tests (t-test), simultaneous tests (F-test), and coefficient of determination (R²). The findings revealed that Qur’an-based character education strengthening partially had no significant effect on the balance of academic and social behavior, with a significance value of 0.488 > 0.05. Meanwhile, emotional intelligence partially had a significant effect on the balance of academic and social behavior, with a significance value of 0.000 < 0.05. Simultaneously, Qur’an-based character education strengthening and emotional intelligence significantly influenced the balance of academic and social behavior, with a significance value of 0.000 < 0.05 and a coefficient of determination (R²) of 0.824. The findings indicate that emotional intelligence plays a dominant role in shaping the behavioral balance of mosque congregants, while Qur’an-based character education requires deeper internalization processes to produce a more optimal impact on social life within the community